HOMA-IR Values in Pregnant Women Based on Body Weight - Lukas, Dwi Lily; Siahaan, Salmon Charles; Rambung, Etha; Alim, Denys Putra; Tannus, Ferdinand Aprianto (Lambung Mangkurat University, 2024)
Insulin resistance plays a crucial role in maternal metabolic adaptation during pregnancy. Underweight pregnant women have metabolic conditions potentially affecting insulin sensitivity and glucose homeostasis. The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) quantitatively measures fasting glucose and insulin levels, providing insights into metabolic health during pregnancy. This study aims to determine the differences in HOMA-IR between underweight and normal-weight pregnant women. The research employs a case design with a quantitative approach, using non-probability sampling techniques including quota and purposive sampling. The total sample comprises 24 participants, divided into 12 underweight pregnant women and 12 normal-weight pregnant women. Statistical analysis shows significant differences between groups: glucose levels (p <0.001), insulin levels (p = 0.018), and HOMA-IR values (p <0.001), all indicating significant findings (p <0.05). The study found differences in glucose and insulin levels between the two groups. Insulin and glucose levels tended to be higher in underweight pregnant women, indicating insulin resistance involvement with higher HOMA-IR levels compared to normal-weight pregnant women. This study can serve as a basis for understanding the patho-mechanism in underweight pregnant women.